L’iceberg e l’angelo benjamiano sulle nuove immagini - Rabbito, Andrea (Scenari, 2021)
Visual Culture Studies analyze the importance of a knowledge of technical images in order to understand the spirit of our time; these studies highlight the need to identify the links that technical images have with the different forms of representation of the past and of the contemporary world.